The Rate of Decline of Sugarbeet Cyst Nematode in Central California Under Nonhost Crops May Impact Biofuel Production - Westerdahl B. B.; Caswell-Chen E. P.; Kegel F. R. (Journal of Nematology)
Crop rotation has been a commercial practice for managing the sugarbeet cyst nematode (Heterodera schachtii, SBCN) since the 1950s. Research conducted in southern California established that SBCN populations decline at the rate of 49% to 80% per year, leading to estimates that three- to four-year rotations to nonhost crops would be sufficient to reduce SBCN densities to nondamaging levels. Following grower reports that much longer rotations were needed in central California, trials were conducted to establish the rate of decline of SBCN in the San Joaquin Valley. Ten commercial fields with a history of SBCN infestation were sampled periodically for up to 6.3 years. In each field, 10 circular subplots located 30.5 meters apart (each with a 6-m radius) were established with reference to a permanent landmark. On each sampling date, 12 subsamples from each subplot were taken randomly from the top 0 cm to 30 cm of soil and composited into a single sample. Standard techniques were utilized to extract and count cysts and eggs from soil samples. Average yearly rates of population decline in the sampled fields ranged from 11.4% to 25.8%. This finding has implications for SBCN management in California sugarbeets grown for biofuel, as the lower decline rates indicate that longer nonhost rotation periods than previously anticipated may be necessary.